2004
DOI: 10.1177/0963662504042690
|View full text |Cite
|
Sign up to set email alerts
|

Science in Society: Re-Evaluating the Deficit Model of Public Attitudes

Abstract: The 'deficit model' of public attitudes towards science has led to controversy over the role of scientific knowledge in explaining lay people's attitudes towards science. The most sustained critique has come from what we refer to as the 'contextualist' perspective. In this view, people's understanding of the ways in which science is embedded within wider political, economic and regulatory settings is fundamental for explaining their attitudes towards science. Most work adopting this perspective has relied on q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
681
3
23

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 928 publications
(720 citation statements)
references
References 34 publications
13
681
3
23
Order By: Relevance
“…Decades of research on the deficit model of communication and understanding have long shown that such simplistic institutional framings are flawed or at least lack necessary nuance (Fischhoff 1995;Sturgis and Allum 2004). The deficit model contends that people perceive something as a problem because they lack knowledge (often scientific) about the issue; thus, providing them with more knowledge will lead them to change their attitudes.…”
Section: Shale Gas Development Public Perceptions and Educationmentioning
confidence: 99%
“…Decades of research on the deficit model of communication and understanding have long shown that such simplistic institutional framings are flawed or at least lack necessary nuance (Fischhoff 1995;Sturgis and Allum 2004). The deficit model contends that people perceive something as a problem because they lack knowledge (often scientific) about the issue; thus, providing them with more knowledge will lead them to change their attitudes.…”
Section: Shale Gas Development Public Perceptions and Educationmentioning
confidence: 99%
“…Unsurprisingly, communicators often assume that a lack of information and understanding explains the lack of public concern and engagement, and that therefore more information and explanation is needed to move people to action. This assumption has been studied widely and is known as the knowledge or information deficit model (Bak 2001;Sturgis and Allum 2004).…”
Section: Inspiration With Informationmentioning
confidence: 99%
“…Early work on public understanding of science viewed the public as essentially deficient in scientific knowledge and requiring scientific education (Irwin and Michael 2003). From this perspective, fears or opposition to scientific or technological innovations could be explained simply in terms of public ignorance of the science and thus could be overcome with sufficient information or education (Sturgis and Allum 2004). This framing of public responses in terms of a deficit of knowledge has been systematically critiqued by ethnographic work, which reveals that ''public uptake (or not) of science is not based on intellectual capability as much as socio-institutional factors having to do with social access, trust and negotiation as opposed to imposed authority'' (Wynne 1991, 116).…”
mentioning
confidence: 99%